2013
DOI: 10.1007/s10620-013-2890-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Sleep Quality in Crohn’s Disease Depends on Disease Activity

Abstract: Impaired sleep quality is associated with active Crohn's disease, but not inactive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 21 publications
0
16
2
Order By: Relevance
“…A majority of these studies utilized validated questionnaires to assess subjective sleep quality including the Pittsburgh Sleep Quality Index (PQSI), the Patient-Reported Outcomes Measurement Information System (PROMIS), the Modified Fatigue Impact Scale (MFIS), or the Epworth Sleepiness Scale (ESS). Data from these studies was consistent and patients with IBD, regardless of whether disease was quiescent or active, reported poorer sleep than healthy controls [5,91,[97][98][99][100][101][102][103][104].…”
Section: Patients With Ibd Report Inadequate Sleepmentioning
confidence: 85%
See 1 more Smart Citation
“…A majority of these studies utilized validated questionnaires to assess subjective sleep quality including the Pittsburgh Sleep Quality Index (PQSI), the Patient-Reported Outcomes Measurement Information System (PROMIS), the Modified Fatigue Impact Scale (MFIS), or the Epworth Sleepiness Scale (ESS). Data from these studies was consistent and patients with IBD, regardless of whether disease was quiescent or active, reported poorer sleep than healthy controls [5,91,[97][98][99][100][101][102][103][104].…”
Section: Patients With Ibd Report Inadequate Sleepmentioning
confidence: 85%
“…In a case-control study, Ranjbaran et al found that subjects with IBD identified prolonged sleep latency, increased fragmentation, use of sleeping aids, and decreased energy as factors associated with poorer overall sleep [91]. Another prospective cohort study corroborated the higher utilization of sleep medications in patients with IBD [100].…”
Section: Patients With Ibd Report Inadequate Sleepmentioning
confidence: 94%
“…4 Several studies in pediatric and adult IBD patients have recorded sleep disturbances in active and inactive IBD. [5][6][7] Indeed, sleepimpaired patients in remission at baseline had an increased risk for disease flare. 8 Similarly, patients with histological evidence of inflammation had sleep disturbances, which were independent of their clinical disease activity status.…”
Section: Nflammatory Bowel Disease (Ibd) Includingmentioning
confidence: 99%
“…In the gastrointestinal tract, significant associations between sleep disturbances and gastroesophageal reflux disease (Fujiwara et al 2012 ), functional dyspepsia (Lacy et al 2011 ), irritable bowel syndrome (Ranjbaran et al 2007a ; Nojkov et al 2010 ), and IBD (Ranjbaran et al 2007a ; Graff et al 2011 ; Ali et al 2013 ; Gingold-Belfer et al 2014 ; Ananthakrishnan et al 2013 , 2014 ) have been reported. Sleep disturbances are commonly found in IBD patients, especially those with active disease (Graff et al 2011 ; Ali et al 2013 ; Gingold-Belfer et al 2014 ; Ananthakrishnan et al 2014 ), and associated with new onset of UC (Ananthakrishnan et al 2014 ) and CD flares (Ananthakrishnan et al 2013 ). However, the prevalence of sleep disturbances in Japanese IBD patients and the association between sleep disturbances and disease flare is unknown.…”
Section: Introductionmentioning
confidence: 99%